EPİFORALI OLGULARDA DİJİTAL SUBSTRAKSİYON MAKRODAKRİYOSİSTOGRAFİ - BAŞAR, Emel; DEMİR, Mehmet; AKMAN, Canan; IŞLAK, Civan; MİRZATAŞ, Çolpan (Cerrahpaşa Medical Journal, 2019)
Background. A group of patients with epiphora were evaluated by a new method of dacryocystography. The technique is digital subtraction macrodacryocystography (DSM) which is based on intubation and injection of radiopaque contrast material into each lacrimal system under the control of direct sequential digitally subtracted imaging. Design. 36 eyes of 18 patients were investigated by DSM. In all of the patients main complaint was epiphora unilaterally or bilaterally. DSM examination was done under the topical anesthesia and DSM method was applied with the digital radiography unit using the low iodine content, a watersoluble contrast material. Results. 24 eyes with epiphora out of 36 examinations were evaluated. 12 eyes out of 24 epiphora cases (50%) were classified as total obstruction of lacrimal passage, 25% of them (3 cases) showed the obstruction at the common canaliculus and 75% of them (9 cases) showed obstruction at the distal of the lacrimal sac. 7 eyes of 24 epiphora cases (30%) showed lacrimal passage stenosis and remainirıg 5 eyes of 24 epiphora cases (20%) showed no stenosis or obstruction despite complaints of epiphora. Conclusion. Reliable and accurate demonstrations of lacrimal duct obstructions were produced by the DSM method. Bone and air free radiographs of lacrimal drainage system can be obtained and they can help the ophthalmic surgeon to decide the lacrimal operation type.